Effect of Pressure, Opportunity, Rationalization and Capability Against Academic Fraud Behavior in Students During Online Lectures - Monica Zuanur Safitri; Wiwik Tiswiyanti; Misni Erwati (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to measure how the influence of pressure, opportunity, rationalization and capability variables on academic fraud behavior in Jambi University accounting students class of 2019 during daring lectures. The research method used is a quantitative method with a sampling technique that is a saturated sample and data collection techniques using a Google form questionnaire. Based on the results of the study, it showed that pressure and opportunity had no significant effect on academic fraud behavior in Jambi University accounting students class of 2019, while rationalization and capabilities had a significant effect on academic fraud behavior on Jambi University of Accounting students class of 2019